SISTEM INFORMASI AKADEMIK SEKOLAH BERBASIS WEB PADA SMP NEGERI 35 PALEMBANG - Fernando, Muhammad Albert; Yulianingsih, Evi (Jurnal Ilmiah Sistem Informasi, 2024)
State Junior High School 35 Palembang is one of the schools in Palembang City, making this school widely chosen by prospective parents of current students because this school has only been opened since 2019. However, the process of processing academic data at this school is still not integrated. The ongoing academic system still uses the Ms. Excel application, without a database. The system development method used is the prototype method, if at the ongoing stage there are shortcomings in the previous stage, additions or improvements can be made directly without having to complete the final stage first. The tool used to describe the system model is in the form of a data flow diagram (FlowMap), in the design of this Academic Information System uses PHP and Mysql programming languages as a database